The Narrative of Daily Dawn over Climate change, FATF and Terrorism in Pakistan perspective during the Year 2022. - khan, Ayaz; Syed Waseem (Journal of Peace, Development and Communication, 2022)
The narratives Daily Dawn which was presented through its editorial were found in majority to be critical in nature to be precise Seventy-seven (77%). The editorials regarding climate change, FATF and Terrorism which was found Fifty-Eight 58 in number. The break up of editorials in 2022 about topics are Forty-Five (45) Terrorism, Six (6) about FATF and Eight (8) about claimant change. All editorial for selected topic were found to be in Four (4) categories as 1. Explanative,2. Criticize, 3. Persuasive, 4. Praise. Unfortunately, majority of the editorial were found unresearched, critical in nature without any alternative plan and answers to questions which was highlighted. It was observed that daily Dawn was not able to educate it readers about the future forecasts and editorials were limited to the report and analysis of events only. Climate changes which was quite clear but it was not the topic before October 2022. And no alternative plan to the peace talks with Taliban (TTP) in response to the criticism daily Dawn indicated. Terrorism still remains the focus point as it the age long phenomenon that hurt Pakistan a lot and it was observed that Forty-five times out of Fifty-Eight in editorials were only about terrorism. Keywords Terrorism, Daily Dawn, agenda setting, climate changes, FATF, news media, analysis of editorials